2017
DOI: 10.14238/pi57.3.2017.149-53
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin, serum nitric oxide, and cognitive function in pediatric thalassemia major

Abstract: Background Hemolysis and repeated blood transfusions in children with thalassemia major cause iron overload in various organs, including the brain, and may lead to neurodegeneration. Hemolysis also causes decreased levels of nitric oxide, which serves as a volume transmitter and slow dynamic modulation, leading to cognitive impairment. Objective To assess for correlations between serum ferritin as well as nitric oxide levels and cognitive function in children with thalassemia major. Methods This analytical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, another study [51] revealed that the IQ score was not correlated with the ferritin serum level. Still, it was correlated with the mean pre-transfusion Hb level, education, and nutritional status [51].…”
Section: Neurophysiology Of Thalassemia Patients and Its Association ...mentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, another study [51] revealed that the IQ score was not correlated with the ferritin serum level. Still, it was correlated with the mean pre-transfusion Hb level, education, and nutritional status [51].…”
Section: Neurophysiology Of Thalassemia Patients and Its Association ...mentioning
confidence: 98%
“…In terms of cognitive ability, a study [50] in children with β-thalassemia major showed that they had lower IQ scores than healthy children, as well as lower verbal comprehension index, processing speed index, perceptual reasoning index, and working memory index [50]. Interestingly, another study [51] revealed that the IQ score was not correlated with the ferritin serum level. Still, it was correlated with the mean pre-transfusion Hb level, education, and nutritional status [51].…”
Section: Neurophysiology Of Thalassemia Patients and Its Association ...mentioning
confidence: 99%
“…An evaluation of thalassemia interventions needs to be conducted as based on the research by Qurbani, Reniarti, Chairulfatah (2017), which studied approximately 40 hemosiderotic thalassemia major patients aged between 6-14 years at the Thalassemia Clinic in Dr. Hasan Sadikin Hospital, Bandung and it showed that 73% had an average Hb level of less than 7,2 g/dl and an average/median serum ferritin level of 3.687 ng/ml before transfusion. This condition i.e.…”
Section: Introductionmentioning
confidence: 99%